PROPERTIES AND CLASSIFICATION OF SOME BARREN SOILS OF KALAMBAINA RIDGE AFTER 25 YEARS OF CONVERSION FROM FOREST TO ARABLE CROPLAND IN KURU-KURU VILLAGE, KWARE, SOKOTO (FUDMA JOURNAL OF SCIENCES, 2020)
Kalambaina ridge was studied at reconnaissance level, covering an area of 25 hectares. Two profile pits (1.5 x 2 x 2 m) were dug at the two different slopes of the four slope segments encountered. These were middle slope and bottom valley. The crest and upper slopes could not be excavated due to their resistance to penetration. Results of the physical properties of the soils indicates a discernable variability in the proportion and distribution of soils particles both at the top and subsoils. The particle size distribution result showed that the pedons have moderate to very high sand content (468 g kg-1 average) at the surface horizons and this irregularly decreases with depth at the subsoil horizons. The porosity of the pedons was generally low, while their bulk density (BD) was generally medium with no definite sequence in distribution. The soils generally are between neutral to strongly alkali in reaction. The dominant exchangeable bases on the exchange complex of the soils were calcium (Ca) and sodium (Na). The organic carbon (OC) content, available phosphorus (AP) and electrical conductivity (EC) of the soils were generally low. However, the cation exchange capacity (CEC) and the total nitrogen (TN) were high. According to USDA Soil Taxonomy system the soils were classified as Typic Aeric Endoaqualfs which correlates with Lixic Lixisols in the WRB system of classification.
Keywords: Alfisols, soil classification, Kalambaina ridge, Kuru-Kuru Kware